Non-intuitive fracture pattern of a failed crane-hanger: A fracture mechanics-based explanation. (October 2015) - Piskoty, G.; Michel, S.A.; Valet, S.; Koster, M.; Sauder, M.; Schindler, H.J.
Highlights: The non-intuitive fracture pattern of a broken hanger was analysed and explained. The manufacturing constrains in the crane hanger were quantified experimentally. The exsisting fracture mechanics solution for a bent shaft was adapted and extended. The fracture toughness of the steel was estimated using a semi empirical theory. The fracture pattern could be explained with the applied residual strength approach. Abstract: A crane hanger in a paper factory failed during service, causing the crash of the transported paper spool weighing 10 tons. Fatigue cracking over 1/3 of the cross section was visible, surprisingly starting at the contact point with the crane hook, where the lifted load produces compressive stresses. This counter-intuitive crack origin could be explained by the manufacturing residual stresses, but still not the final fracture of the hanger. The fractography by SEM revealed a multi-modal fracture pattern, including a cleavage fast crack region, surprisingly sandwiched between two sections of fatigue cracking. For explanation of this non-intuitive pattern, a residual strength approach has been chosen. For this, the bending moment " M " due to the manufacturing constraints and the corresponding bending resistance " M c " of the hanger's critical cross section were determined as a function of the crack length " a ". The function M ( a ) was computed with a finite element model of the cracked hanger. The function M c ( a ) was defined by means of fracture mechanics methodology. The stress intensity model is based upon the existing solution of a shaft in bending, adapted for the curved shape of the hanger's arch and extended for deep cracks using the compounding technique. In order to find the conditions for on-set and arrest of the crack, the stress intensity was replaced by the fracture toughness of the steel. This material property was estimated using a semi empirical theory, which uses classical mechanical steel properties and accounts for the effect of the thickness and dynamic loading on fracture toughness. The cross points of the obtained M ( a ) and the M c ( a ) curves in the residual strength diagram correlate well with the observed crack lengths both at on-set and at arrest of brittle fast cracking between phases of fatigue cracking. This consistency indicates the general suitability of the proposed fracture mechanics model.